LLaVA-GM: lightweight LLaVA multimodal architecture - Han, Zhiyin; Liu, Xiaoqun; Hao, Juan (Frontiers in Computer Science, 2025)
Multimodal large-scale language modeling has become the mainstream approach in natural language processing tasks and has been applied to various cross-modal fields such as image description and visual question answering. However, large-scale language modeling has high computational complexity and a large operational scale, which presents significant challenges for deployment in many resource-constrained scenarios. To address such problems, a lightweight multimodal framework, LLaVA-GM, is proposed, based on LLaVA, which can be deployed on devices with low resource requirements and has greatly reduced model parameters. It can also be tested on common VQA tasks and achieves good performance. The main contributions and work are as follows: First, it is found that the backbone of the Vicuna language model in LLaVA is too redundant. When fine-tuning downstream tasks, a very small amount of data sets is difficult to affect the language model. It is replaced with a new Gemma language model, thereby achieving fast task-specific adaptation with fewer parameters and data. Second, in response to the problem of information redundancy, the MoE mixed expert model is introduced. This model can be used in combination with itself, combining the MoE mixed expert model with Gemma to reduce the amount of computation while maintaining performance. Directly training the entire model will lead to a decline in performance. A multi-stage training strategy is adopted to maintain performance. First, the MLP layer is trained for visual adaptation, then the entire Gemma model is trained to improve multimodal capabilities, and finally only the MoE layer is trained for sparsification to ensure a smooth transition from dense models to sparse models. The experiment was tested on multiple VQA datasets and achieved good performance, confirming the potential of this compact model in downstream multimodal applications.